Teacher Quality, Instructional Quality and Student Outcomes Relationships Across Countries, Cohorts and Time - Nilsen, Trude; Gustafsson, Jan-Eric (IEA Research for Education, A Series of In-depth Analyses Based on Data of the International Association for the Evaluation of Educational Achievement (IEA), 2016)
This volume offers insights from modeling relations between teacher quality, instructional quality and student outcomes in mathematics across countries. The relations explored take the educational context, such as school climate, into account. The International Association for the Evaluation of Educational Achievement’s Trends in Mathematics and Science Study (TIMSS) is the only international large-scale study possessing a design framework that enables investigation of relations between teachers, their teaching, and student outcomes in mathematics. TIMSS provides both student achievement data and contextual background data from schools, teachers, students and parents, for over 60 countries. This book makes a major contribution to the field of educational effectiveness, especially teaching effectiveness, where cross-cultural comparisons are scarce. For readers interested in teacher quality, instructional quality, and student achievement and motivation in mathematics, the comparisons across cultures, grades, and time are insightful and thought-provoking. For readers interested in methodology, the advanced analytical methods, combined with application of methods new to educational research, illustrate interesting novel directions in methodology and the secondary analysis of international large-scale assessment (ILSA).  .